How does the landscape uniformity in different forest landscapes affect the visual behavior and preference evaluation intention of participants—a case study of forest landscape in northern China (Liaoning) - Gao, Yu; Sun, Xiaomei; Zhang, Zhi; Zhang, Weikang; Meng, Huan; Zhang, Tong (Frontiers in Forests and Global Change, 2024)
Background High-quality in-forest landscapes are very important when landscape designers and foresters are planning and managing forest landscape resources. Understanding people’s visual behavior toward in-forest landscapes plays an important role in creating high-quality in-forest landscapes. Methods People’s visual information about in-forest landscapes with different landscape uniformity (IFLDLU) was visualized and digitized by eye-tracking technology and virtual reality method of picture, and the data were statistically analyzed by MANOVA, one-way ANOVA, Spearman’s rho correlation analysis, and linear regression in SPSS. Purpose This study aimed to discuss the influence of landscape uniformity on people’s visual behavior, satisfaction preference, and re-viewing intention, and to reveal the main reasons for the spatial cognitive characteristics of in-forest scenes that arouse their visual attention and re-viewing intention. Main results (1) The landscape uniformity of the in-forest landscape (IFL) affects people’s observation mode; (2) People’s visual attention differs across in-forest landscape uniformity, as mainly reflected in visual span and pupil diameter; (3) Overall, people prefer a cluster distribution of in-forest landscapes, for which they have higher re-viewing intentions; (4) Spatial cognitive characteristics that arouse participants’ visual behavior, satisfaction preference, and re-viewing intention vary with the landscape uniformity of in-forest landscapes. Among them, many spatial cognitive characteristics should be optimized in random distribution for IFL, arousing higher satisfaction preference and re-viewing intention. Therefore, when planning, designing, and managing in-forest landscapes, we suggest that spatial cognitive characteristics should be improved and optimized based on the landscape uniformity of the IFL to arouse participants’ positive visual attention, enhance their place identity, make them “reluctant to bid farewell,” and further arouse their place attachment.